Simplified analysis of mid-story seismically isolated buildings. - Wang, Shiang-Jung
The mid-story isolation design method is recently gaining popularity for the seismic protective design of buildings located in the areas of high population. In a mid-story isolated building, the isolation system is incorporated into the mid-story rather than the base of the building. In this paper, the dynamic characteristics and seismic responses of mid-story isolated buildings are investigated using a simplified three-lumped-mass structural model for which equivalent linear properties are formulated. From the parametric study, it is found that the nominal frequencies of the superstructure and the substructure, respectively, above and below the isolation system have significant influences on the isolation frequency and equivalent damping ratio of a mid-story isolated building. Moreover, the mass and stiffness of the substructure are of greater significance than the superstructure in affecting the dynamic characteristics of the isolated building. Besides, based on the response spectrum analysis, it is noted that the higher mode responses may contribute significantly to the story shear force of the substructure. Consequently, the equivalent lateral force procedure of design codes should carefully include the effects of higher modes.
Keywords: Mid-story isolation; Seismic design; Structural control; Base isolation